단안 망막정맥폐쇄환자 반대안의 빛간섭단층혈관조영술을 통한 망막모세혈관분포 분석 - 정우현(Woo Hyun Jung), 김정림(Jung Lim Kim) (Daihan angwa haghoi jabji, 2020)
목적: 단안 망막분지정맥폐쇄환자의 반대안과 대조군에서 빛간섭단층혈관조영술을 이용하여 망막모세혈관분포를 비교하고자 하였다. 대상과 방법: 단안 망막분지정맥폐쇄로 진단 받은 환자(38명, 38안)와 검진 목적으로 검사를 시행 받았던 경우(37명, 37안)를 대조군으로 후향적으로 비교하였다. 스펙트럼영역 빛간섭단층촬영기를 이용하여 신경절세포-내망상층의 두께를 측정하였고 빛간섭단층혈관조영술을 이용하여 황반오목으로부터 반경 0.5 mm 이내의 중심 영역 및 반경 1-1.5 mm의 주변 영역, 반경 3 mm 이내의 총 영역 각각의 혈관밀도 및 관류밀도, 오목무혈관부위(FAZ)의 면적 및 둘레를 측정하여 비교 분석하였다. 결과: 단안 망막분지정맥폐쇄가 있는 환자와 비교하였을 때 고혈압의 유병률은 단안 망막분지정맥폐쇄가 있는 환자에서 대조안보다 유의하게 많았으며(p=0.014), 신경절세포-내망상층의 두께를 비교하였을 때는 양 군의 의미 있는 차이를 보이지 않았다. 빛간섭단층혈관조영술 환자군 간의 혈관밀도와 관류밀도는 의미 있는 차이를 보이지 않았으나 중심오목무혈관부위의 넓이와 둘레는 단안 망막분지정맥폐쇄가 있는 환자에서 대조안보다 유의하게 넓게 나타났다(p=0.048, p=0.011). 결론: 망막분지정맥폐쇄환자들의 반대안에서 정상 대조군에 비해 신경절세포-내망상층의 두께의 유의미한 변화는 없으나, 중심오목무혈관부위의 넓이와 둘레가 증가되어 있었으므로 단안에 국한된 망막정맥폐쇄환자에서도 반대안의 허혈성 질환에 대한 주의깊은 관찰이 필요하며, 위험 인자의 관리 및 혈류 개선을 위한 노력이 필요할 것으로 생각된다. Purpose: To compare the thickness of the ganglion cell-inner plexiform layer (GCIPL) and the perifoveolar retinal capillary network between fellow eyes with unilateral branch retinal vein occlusion (BRVO) and healthy control eyes using optical coherence tomography angiography (OCTA). Methods: Retrospective cross-sectional study including 38 patients diagnosed with unilateral BRVO and 37 control subjects. We investigated the thicknesses of the GCIPL layer using OCT, also the vascular density (VD), perfusion density (PD), area and perimeter of the foveal avascular zone (FAZ) using the OCTA. Results: Patients with unilateral BRVO had a higher incidence of hypertension. In the fellow eyes of the unilateral BRVO patients, the area and perimeter of the FAZ were wider and longer than for the control eyes. There was no significant difference in the GCIPL thickness, VD and PD between the two groups. Conclusions: There is no significant change in the thickness of GCIPL between 2 groups, the fellow eyes of the unilateral BRVO patients have the larger area and longer perimeter of the FAZ instead. This means macular ischemia in the follow eye when the BRVO existed. Therefore, ischemic diseases should be carefully monitored in the fellow eyes of unilateral BRVO patients. KCI Citation Count: 0